2016
DOI: 10.1038/ejhg.2016.97
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities in hepatic cysts point to novel polycystic liver disease genes

Abstract: Autosomal dominant polycystic liver disease (ADPLD) is caused by variants in PRKCSH, SEC63, and LRP5, whereas autosomal dominant polycystic kidney disease is caused by variants in PKD1 and PKD2. Liver cyst development in these disorders is explained by somatic loss-of-heterozygosity (LOH) of the wild-type allele in the developing cyst. We hypothesize that we can use this mechanism to identify novel disease genes that reside in LOH regions. In this study, we aim to map abnormal genomic regions using high-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Similarly, Sze et al ( 22 ) suggested that MAD2 deficiency may cause a mitotic checkpoint defect in hepatoma cells. Wills et al ( 23 ) suggested that BUB1, a loss-of-heterozygosity driver gene, may be implicated in the germline causes of genetic instability in polycystic liver disease. Furthermore, Wang et al ( 24 ) identified that BUB1B activated parathyroid hormone like hormone to promote the G-protein-coupled receptor-induced loss of cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sze et al ( 22 ) suggested that MAD2 deficiency may cause a mitotic checkpoint defect in hepatoma cells. Wills et al ( 23 ) suggested that BUB1, a loss-of-heterozygosity driver gene, may be implicated in the germline causes of genetic instability in polycystic liver disease. Furthermore, Wang et al ( 24 ) identified that BUB1B activated parathyroid hormone like hormone to promote the G-protein-coupled receptor-induced loss of cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…Since these seminal papers, altered protocols have enabled the establishment of liver models from different species from rat to dog (Nantasanti et al, 2015; Kuijk et al, 2016; Kruitwagen et al, 2017), as well as human disease models ranging from alpha-1-antitrypsin (A1AT) deficiency and Alagille syndrome (Huch et al, 2015) to polycystic liver disease (Wills et al, 2016) or cancer (Broutier et al, 2017; Nuciforo et al, 2018). By modifying the Huch conditions to expand human organoids (Huch et al, 2015), the Vallier lab has recently established extrahepatic biliary organoids and showed that these can form bile-duct-like tubes that can reconstruct the gallbladder wall upon transplantation into mice (Sampaziotis et al, 2017a).…”
Section: Endoderm-derived Organoidsmentioning
confidence: 99%
“…Based on previous studies showing that cystic cholangiocytes in polycystic liver disease have abnormal cell cycle profiles and malfunctioning cilia, Gradilone and collaborators (9) studied the role of HDAC6 in polycystic liver disease (PLD), which targets the epithelial lining of the biliary tree (41). They found that expression of the HDAC6 protein is six times higher in cystic liver tissue and in cultured cholangiocytes isolated from both PCK rats (an animal model of PLD) and humans with PLD.…”
mentioning
confidence: 99%